2022
DOI: 10.1088/1674-1056/ac76a9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of secondary electron emission from few layer graphene on silicon (111) surface

Abstract: As a typical 2D coating material, graphene has been utilized to effectively reduce secondary electron emission from the surface. Nevertheless, the microscopic mechanism and the dominant factor of secondary electron emission suppression remain controversial. Since traditional models rely on experimental bulk properties data which is scarcely appropriate for the 2D coating situation, this paper presents a first-principles based numerical calculation of the electron interaction and emission process for monolayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…For a quantitative description of the SEY, the Monte Carlo method combined with scattering cross-section calculations would be the primary option. [45] However, because of the low doping concentration of our samples in the range between 0.781% and 3.125%, the doping systems (B(N)-doped Si wafers) constructed for the Monte Carlo simulations would be too large to properly account for the electron scattering by the impurities, which is computationally costly. Therefore, we theoretically studied the physical mechanism of N substitution in Si using first-principles calculations, and then experimentally investigated its effect on the structural and electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…For a quantitative description of the SEY, the Monte Carlo method combined with scattering cross-section calculations would be the primary option. [45] However, because of the low doping concentration of our samples in the range between 0.781% and 3.125%, the doping systems (B(N)-doped Si wafers) constructed for the Monte Carlo simulations would be too large to properly account for the electron scattering by the impurities, which is computationally costly. Therefore, we theoretically studied the physical mechanism of N substitution in Si using first-principles calculations, and then experimentally investigated its effect on the structural and electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene is widely used in electronic devices due to its excellent electrical properties, extremely high surface conductivity, and high thermal conductivity [34,35]. In our previous study, we also found that graphene has a good performance in suppressing secondary electrons [36,37]. However, in addition to the contribution of secondary electron emission, the microwave resonance-induced discharge is also closely related to the ionization excitation of electrons-gas collision [38].…”
Section: Introductionmentioning
confidence: 88%